Requirement Model for Online Neighbourhood Association and Volunteer Patrolling Scheme Management System in JPNIN - Muhamad Ashraff, Abd. Ghani (2009)
In new era of modern technology, most of public services in Malaysia are moving forward in applying information technology concept such as information system, expert system, real time and mobile technology. This is because most of all Malaysian government ministries and departments have a vision to reduce the percentage of digital divided that occurs among Malaysian citizen especially those that live in rural areas. Jabatan Perpaduan Negara dan Integrasi Nasional (JPNIN) is one of Malaysian government ministry department that responsible for managing and monitoring the issues that are related to internal politics in Malaysia especially in handling multi races issues and integrity of Malaysian citizen to make sure Malaysian stay in peace and harmony. JPNIN is also responsible to monitor and manage the information that is related to Neighbourhood Association (NA) and Volunteer Patrolling Scheme (VPS) in all state of Malaysia. There proposal management system will be utilizing web-based concept that can be applied to NA and VPS. This web-based application will be enable JPNIN staff officers to manage the information that related with NA and VPS via internet.